2011
DOI: 10.1039/c1cc11955a
|View full text |Cite
|
Sign up to set email alerts
|

Three-component coupling using arynes and DMF: straightforward access to coumarins via ortho-quinone methides

Abstract: ortho-Quinone methides, arising from a formal [2+2] cycloaddition between arynes and DMF, were found to facilely undergo a [4+2] cycloaddition with ester enolates or ketenimine anions to produce diverse coumarins in a straightforward manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(53 citation statements)
references
References 25 publications
0
52
0
1
Order By: Relevance
“…[48] Arylacetonitriles were found to be suitable as Scheme 27. Proposed mechanism for the direct transformation of DMF into a CN group.…”
Section: Reactions With Arynesmentioning
confidence: 99%
“…[48] Arylacetonitriles were found to be suitable as Scheme 27. Proposed mechanism for the direct transformation of DMF into a CN group.…”
Section: Reactions With Arynesmentioning
confidence: 99%
“…[9] Bifunctional α-amino carbonitriles are not only key intermediates in the preparation of α-amino acids, but they also play important roles in constructing various heterocycles because of their dual functionality. [9] Bifunctional α-amino carbonitriles are not only key intermediates in the preparation of α-amino acids, but they also play important roles in constructing various heterocycles because of their dual functionality.…”
Section: Introductionmentioning
confidence: 99%
“…hydrochloric acid and ethanol. Yoshida et al [77], have also been reported the synthesis of 173a through the reaction of 1 with 2-(trimethylsilyl)phenyl-trifluoro-methane-sulfonate (174) in DMF containing potassium fluoride (Scheme 38).…”
Section: Synthesis Of Coumarin Derivativesmentioning
confidence: 96%